2022
DOI: 10.1108/compel-07-2021-0257
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid particle swarm optimization rat search algorithm for parameter estimation of solar PV and fuel cell model

Abstract: Purpose The purpose of the proposed hybrid method aims to increase population efficiency, and a local search is used to further improve the value of the global best solution. An experimental observation suggests that the model’s statistical outcomes are more aligned with the real-time experimental findings. Design/methodology/approach A novel metaheuristic efficient hybrid algorithm, i.e. hybrid particle swarm optimization rat search algorithm, is introduced and applied for parameter extraction of hybrid ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Different metaheuristic algorithms for non-parametric statistical tests were used to verify the discovery of the result parameters. According to the experimental observations mentioned in the abstract, the statistical results of this model were more consistent with the real-time experimental results [6]. Sun, Y et al proposed a two-stage approach to improve the PSO.…”
Section: Related Worksupporting
confidence: 69%
“…Different metaheuristic algorithms for non-parametric statistical tests were used to verify the discovery of the result parameters. According to the experimental observations mentioned in the abstract, the statistical results of this model were more consistent with the real-time experimental results [6]. Sun, Y et al proposed a two-stage approach to improve the PSO.…”
Section: Related Worksupporting
confidence: 69%
“…The hybrid algorithm is far better than the standalone algorithm with respect to convergence time, reliability, and memory etc. After the extraction of both the models the Friedman ranking test [ 40 – 44 ] Table 8 and Wilcoxon’s rank sum test [ 45 51 ] Table 9 is performed and from this test also it is concluded that the proposed hybrid algorithm is far better than the rest of the compared standalone algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…Table 13 shows the statistical analysis results from the PEMFC parameter estimation done using the Friedman Ranking Test [37][38][39][40] for both of the fuel cell models. First place is secured by HPSOPF, followed by PSOGWO, GWOCS, PF, GWO, and PSO.…”
Section: Discussionmentioning
confidence: 99%